PENGARUH INTENSITAS PAPARAN ROKOK TERHADAP KAPASITAS KARDIORESPIRASI MAHASISWA PENJASKESREK - Fazryani Mazita Torano; Siane Maria Tampi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Smoking behavior among university students remains a significant public health issue, including among students of Physical Education, Health, and Recreation (Penjaskesrek), who are expected to maintain optimal physical fitness and healthy lifestyles. Continuous exposure to cigarette smoke may negatively affect cardiorespiratory function by impairing oxygen transport and reducing aerobic endurance. This study aimed to determine the effect of smoking exposure intensity on the cardiorespiratory capacity of Penjaskesrek students. This research employed a quantitative analytic observational design with a cross-sectional approach. The study involved 40 Penjaskesrek students selected through purposive sampling. Smoking exposure intensity was measured using the Brinkman Index based on the number of cigarettes consumed per day and duration of smoking, while cardiorespiratory capacity was assessed using the Multistage Fitness Test (bleep test) to estimate VO₂max values. Data were analyzed using Pearson correlation analysis with a significance level of 0.05. The results showed that 65% of respondents were classified as light smokers and 35% as moderate smokers. Most respondents had moderate cardiorespiratory capacity levels. Statistical analysis revealed a significant negative correlation between smoking exposure intensity and cardiorespiratory capacity (r = -0.648; p = 0.001). Students with moderate smoking intensity demonstrated lower mean VO₂max values compared to light smokers. These findings indicate that higher smoking exposure intensity contributes to decreased cardiorespiratory capacity among Penjaskesrek students. Therefore, health promotion and smoking prevention programs are necessary to improve students’ awareness of the adverse effects of smoking on physical fitness and long-term health.